Introductory Emergency Medicine Clinical Skills Course: A Daylong Course Introducing Preclinical Medical Students to the Role of First Responders - Hina Ghory; Wallace Carter; Lyuba Konopasek; Yoon Kang; Neal Flomenbaum; Jeremy Sperling (Association of American Medical Colleges, 2017)
Introduction A complete medical school curriculum must include an introduction to first aid; the management of airway, breathing, and circulation; and basic medical emergencies. The September 11, 2001, terrorist attacks in New York underscored the need for such training for US students even in their preclinical years. During that tragedy, many Weill Cornell Medical College (WCMC) preclinical students were eager to volunteer at Ground Zero and in the emergency department, yet it was clear they were not prepared for even basic medical emergencies this early in their training. To address this gap, in 2002 we incorporated this expanded first-responder course into the first-year doctoring class at WCMC. Methods The course includes a morning of lectures followed by related workshops. Students also practice managing ill patients in multiple case scenarios and participate in a tabletop disaster-management exercise. Results This course has become a mainstay of our first-year curriculum, receiving high praise from students annually. It generates tremendous interest in emergency medicine and lays a foundation of basic emergency medicine knowledge for students at an early point in their education. Discussion The unique experience of our medical school during the 9/11 tragedy highlighted the need for a course that would introduce preclinical medical students to the basic skills needed to assist in emergency scenarios in the field. Over the past 13 years, this course has developed into an essential part of our preclinical curriculum and has been strengthened through changes made based on student feedback.